Comparative Analysis on Discharge Gas Production Characteristics of Typical Electrodes with Oil Insulation - Qin LIU; Xiongjie XIE; Wei HU; Taiwei LIU; Xiaoqing LUO; Qiming YE (Zhongguo dianli)
The oil-less equipment is internally insulated by filling with insulating oil. The discharge or overheating faults may cause the degradation of insulating oil, consequently producing a large amount of dissolved gases such as H2, hydrocarbon gas, CO and CO2, and equipment explosion may occur in severe cases due to the small internal space, resulting in huge economical loss. Therefore, a discharge test system is designed for oil-less equipment to obtain the gas diffusion characteristics in the oil after discharge. A comparative study is conducted on the gas production for three typical electrodes, including the plate-plate electrode, ball-ball electrode and needle-plate electrode, with different gap distances and different discharge time. The research results show that under plate-plate electrode discharge, the gas produced by direct pressurization to breakdown is small in volume; the content of C2H2 and H2 produced by the ball-ball electrode and needle-plate electrode discharge tends to be saturated; under same gap distance and discharge time, the needle-plate electrode produces the largest volume of gas, followed by the ball-ball electrode, and the plate-plate electrode produces the least; at 1mm gap, the discharge process of ball pure oil ball is more intense than that of ball paperboard ball with large gas production. The variation characteristics of the discharge gas content in three typical electrode oils are thus obtained. The reached conclusions have great significance for the fault analysis of oil-less equipment under gas production.